A Second Case of Human Conjunctival Infestation With Thelazia gulosa and a Review of T. gulosa in North America. (22nd October 2019) - Bradbury, Richard S; Gustafson, Dianne Travers; Sapp, Sarah G H; Fox, Mark; de Almeida, Marcos; Boyce, Michelle; Iwen, Peter; Herrera, Vicki; Ndubuisi, Mackevin; Bishop, Henry S
Abstract: We describe a second case of human infection caused by Thelazia gulosa (the cattle eye worm), likely acquired in California. For epidemiologic purposes, it is important to identify all Thelazia recovered from humans in North America to the species level.